Nodular typhlitis from Heterakis isolonche - Buckner, Sydney R.; Edwards, Erin E. (Brazilian Journal of Veterinary Pathology, 2025)
A captive, 4-year-old, 1 kg, female, Bornean crested fireback pheasant (Lophura ignita) with no previous medicalhistory was presented for necropsy.